Diabetes dieta e sabor: receitas para desjejum e lanches - Hoffmann, Lucia Maria (Universidade do Vale do Rio dos Sinos, 2011)
Diabetes mellitus (DM) is a chronic disease that currently affects millions of people worldwide, projected to reach 4.4% of the population in 2030. Currently in Brazil the prevalence of DM is 7 to 8% of the population. The increase of overweight and obesity rates associated with changes in lifestyle and population aging are the main factors behind the increasing prevalence of type 2 diabetes mellitus (T2DM). The changes in dietary of the Brazilian population, as the low frequency of high-fiber foods, increase the proportion of fats and sugars in the diet, coupled with sedentary lifestyle consists in one of main risk factors of T2DM, obesity and other chronic diseases. The various diet recipes of breads and cakes presented here are intended to assist in the preparation of the meal plan of patients with DM2 and choosing foods with lower glycemic index, and lower rate of simple sugars. Although we find many processed food ready for consumption on the market, to attend people with type 2 diabetes, this work contributes with recipes of breads and pastries for breakfast and snacks with low glycemic ingredients, easy to perform, well accepted by taste, and reach the social aspects as the need to indulge in the pleasures of eating. Recipes of breads and cakes were prepared free of simple sugars (glucose, sucrose, fructose), which characterizes them as diet, according to the National Health Surveillance Agency (ANVISA). Also in its formulation part of the simple carbohydrates were replaced by complex carbohydrates found in whole wheat flour, oat flour, rye flour, quinoa flakes, spices, seeds, oil seeds, in order to slow its absorption into the body preventing spikes in blood glucose in diabetic patients. To motivate and encourage adherence to the diet, the eating habits of patients with DM should not undergo drastic changes. For this, the combination of ingredients in each recipe gives the product a pleasant taste similar to those made with sucrose, thus motivating its use, not only by the holder of DM2, but for your whole family and it encourages social interaction at the time of meal.
Keywords: Diabetes mellitus tipo 2; Índice glicêmico; Adesão à dieta; Diabetes mellitus type 2; Glycemic index; Adherence to the diet